Analysis of the Influence of Psychological Bias on Crash-Prone Behaviour in the Cryptocurrency Market with Risk Perception as a Moderator - Bunyamin; Mauludin, Hanif; Nanda Maryana, Vica Maizhatin (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines psychological determinants of crash-prone behaviour by integrating Prospect Theory and Cumulative Prospect Theory. Using PLS-SEM on survey data, it investigates the effects of herding, loss aversion, reflection effect, and risk perception, with risk perception as a moderator. Results show all factors significantly increase crash-prone behaviour, with risk perception as the strongest predictor. Risk perception amplifies loss aversion but does not moderate herding. Notably, it negatively moderates the reflection effect, challenging classical Prospect Theory. These findings offer theoretical advancement and practical implications for designing behavioural interventions and policies to enhance stability in financial markets.